Immune-neuroendocrine reactivity and features of tuberculosis in pregnancy - Starshinova, Anna; Churilov, Leonid P.; Kudryavtsev, Igor; Rubinstein, Artem; Belyaeva, Ekaterina; Kulpina, Anastasia; Ling, Hong; Zhuang, Min; Kudlay, Dmitry (Frontiers in Medicine, 2025)
The combination of tuberculosis and pregnancy always raises questions about therapy, the specialness of management of pregnancy, obstetrics, postpartum period, and lactation; the effect of therapy on fetal development and the peculiarities of the tuberculosis course. Until recently, tuberculosis and pregnancy were considered a rare combination, but with the growing problem of HIV infection and worsening tuberculosis screening among adults, this combination has become quite common. Moreover, cases of congenital tuberculosis in newborns have begun to emerge. In this review, we analyzed features of immunologic and immuno-neuroendocrine reactivity in pregnant women that influence for prevalence TB and TB/HIV coinfection. The immuno-neuroendocrine changes characteristic of pregnancy have a multifactorial effect on antituberculosis immunity and determine the specificity of the course of tuberculosis against the background of pregnancy. These changes contribute to a more severe course of TB than before pregnancy. The structure of TB clinical forms in women who became ill during pregnancy and in the first year after childbirth is characterized by greater severity, higher frequency of multi-organ lesions, and the percentage of bacterial isolates is significantly higher among women with TB that developed in the postpartum period compared to women who developed it during pregnancy. HIV infection poses a particular threat, exacerbating immune response disorders that affect the effectiveness of treatment and disease progression in general.